Estudo químico de constituintes das cascas do caule de Aristolochia esperanzae Kuntze (Aristolochiaceae), empregando métodos espectroscópicos e teóricos - Alison Geraldo Pacheco (2013)
The species Aristolochia esperanzae is widely used for the treatment of rheumatic diseases. This work describes the chromatographic isolation of the chemical constituents of the stem bark of this plant and structural analysis of the obtained phytochemicals. Chromatographic fractionation of less polar fractions of the ethanolic extract provides lignans, aristolochic acids, aristolactams, diterpenes, and triterpenes which were previously reported by the our research group. In this present work, the phytochemical study of medium polarity fractions was carried out, providing lignans (-and -cubebin), aristolochic acid (3-hydroxy-4-methoxy-10-nitrofenantreno 1 - carboxylic) and phenol derivatives dimer (2,2', 6,6'-tetra-tert-butyl-4,4'-etilenodifenol and 5,5'-dihydroxy-1H, 1H'-2, 2'-biindeno-1,1'-dione). Structural analysis of these compounds was mainly based on nuclear magnetic resonance of hydrogen and carbon-13, HSQC, HMBC, NOESY, and COSY techniques. Aristolochic acid and ketone dimer have not been recorded in the literature, being then new compounds. Structural analysis of these compounds and pentacyclic triterpenes was also performed by molecular modeling techniques.